218k views
5 votes
Solve the following inequality for n. Write your answer in the simplest form.9n + 4 ≤ 6n - 6

User Nekoro
by
5.0k points

1 Answer

5 votes

Given,

The expression is,


9n+4\le6n-6

Substracting 4 from both sides then,


\begin{gathered} 9n+4-4\le6n-6-4 \\ 9n\le6n-10 \end{gathered}

Substracting 6n from both sides then,


\begin{gathered} 9n\le6n-10 \\ 9n-6n\le6n-6n-10 \\ 3n\le-10 \end{gathered}

Multiplying both sides by 1/3 then,


\begin{gathered} 3n\le-10 \\ 3n*(1)/(3)\le-10*(1)/(3) \\ n\le-(10)/(3) \end{gathered}

Hence, the solution for n is n<= (-10/3).

User Ricka
by
5.3k points